The Story of Summer Visions: The Creation of a New Public in a Community-Engaged Youth Media Program (LEARNing Landscapes, 2016)
Over the course of the last two decades, youth media programs have become increasingly popular as models for community-engaged digital storytelling projects. This narrative re ection is based on the author’s experience as the creative mentor and story editor within a nationally recognized youth-run media production program. Drawing on Arendt’s (1954) thinking on the educative project and on Poyntz’s (2009) argument that holds "agonistic struggle" over creative expression within a community of youth engagement is critical to developing a shared sense of the world. This narrative re ects on the collective work of story creation within a community-engaged media art practice as a vehicle for developing capacity to hold pluralistic points of view, perspective, and voice essential for the sustainment of democratic movements.
Keywords: youth; media; reflection; narrative; engagement; story